DO CHINESE ELECTRIC VEHICLE SALES INFLUENCE AUTOMOTIVE STOCK RETURNS IN INDONESIA? EVIDENCE FROM LISTED AUTOMOTIVE FIRMS - Hardito, Haikal Alfian; Yanthi, Merlyana Dwinda (PT Wahana Global Education, 2026)
This study aims to obtain empirical evidence regarding the influence of Chinese electric car sales on stock returns of automotive issuers in Indonesia and to examine the differences in average stock returns before and after the sales increase. The study uses a comparative quantitative approach with secondary data in the form of annual stock prices of nine automotive companies listed on the Indonesia Stock Exchange for the period 2018–2025. The sample was selected using purposive sampling. Data analysis was performed using linear regression and paired sample t-tests using SPSS 26. The results show that Chinese electric car sales do not significantly affect stock returns. However, a difference test indicates a significant difference in average stock returns before and after the sales increase. Based on company size, a significant difference was found in small companies, while no significant difference was found in large companies. These findings indicate that the Indonesian capital market has not responded significantly to the direct influence of Chinese electric car sales despite changes in stock returns between periods.